Novel pathogenic SMAD2 variants in five families with arterial aneurysm and dissection: further delineation of the phenotype. Issue 4 (2nd July 2018) - Cannaerts, Elyssa; Kempers, Marlies; Maugeri, Alessandra; Marcelis, Carlo; Gardeitchik, Thatjana; Richer, Julie; Micha, Dimitra; Beauchesne, Luc; Timmermans, Janneke; Vermeersch, Paul; Meyten, Nathalie; Chénier, Sébastien; et al.
Abstract : Background: Missense variants in SMAD2, encoding a key transcriptional regulator of transforming growth factor beta signalling, were recently reported to cause arterial aneurysmal disease. Objectives: The aims of the study were to identify the genetic disease cause in families with aortic/arterial aneurysmal disease and to further define SMAD2 genotype–phenotype correlations. Methods and results: Using gene panel sequencing, we identified a SMAD2 nonsense variant and four SMAD2 missense variants, all affecting highly conserved amino acids in the MH2 domain. The premature stop codon (c.612dup; p.(Asn205*)) was identified in a marfanoid patient with aortic root dilatation and in his affected father. A p.(Asn318Lys) missense variant was found in a Marfan syndrome (MFS)-like case who presented with aortic root aneurysm and in her affected daughter with marfanoid features and mild aortic dilatation. In a man clinically diagnosed with Loeys-Dietz syndrome (LDS) that presents with aortic root dilatation and marked tortuosity of the neck vessels, another missense variant, p.(Ser397Tyr), was identified. This variant was also found in his affected daughter with hypertelorism and arterial tortuosity, as well as his affected mother. The third missense variant, p.(Asn361Thr), was discovered in a man presenting with coronary artery dissection. Variant genotyping in three unaffected family members confirmed its absence. The last missense variant, p.(Ser467Leu), was identified in a man with significant cardiovascular and connective tissue involvement. Conclusion: Taken together, our data suggest that heterozygous loss-of-function SMAD2 variants can cause a wide spectrum of autosomal dominant aortic and arterial aneurysmal disease, combined with connective tissue findings reminiscent of MFS and LDS.